Strength of association between the Five-Times-Sit-to-Stand Test and balance, knee extensor strength and lower limb power in community-dwelling older adults. (2nd March 2019) - Tiwari, Devashish; Talley, Susan Ann; Alsalaheen, Bara; Goldberg, Allon
Abstract : Background/Aims: Although strength, power and balance are associated with the Five-Times-Sit-to-Stand Test in older adults, the relative contribution of each to sit-to-stand performance is unclear. This study compared the strength of association between the Five-Times-Sit-to-Stand Test and measures of balance, knee extensor strength, and lower limb power in older adults. Methods: A total of 41 community-dwelling older adults completed the Five-Times-Sit-to-Stand Test and tests of balance, knee extensor strength, and lower limb power. Results: The strongest association observed was between the Five-Times-Sit-to-Stand Test and dynamic balance ( rs = −0.61, P <0.001), with a moderate association observed between the Five-Times-Sit-to-Stand Test and power ( rs = −0.52, P =0.001). Conclusions: Dynamic balance and lower limb power are determinants of, and play roles in the Five-Times-Sit-to-Stand Test performance in community-dwelling older adults. Dynamic balance was the strongest determinant of Five-Times-Sit-to-Stand Test performance, suggesting that the Five-Times-Sit-to-Stand Test should not be viewed solely as a proxy measure of knee extensor strength in community-dwelling older adults.